Sodium-ion battery positive electrode material and preparation method thereof, positive plate and negative-electrode-free sodium-ion battery
By introducing a sodium lanthanum zirconium oxygen clad layer into the positive electrode material of sodium ion battery, the problems of Ni2+, Fe3+ dissolution and uneven deposition of sodium dendrites in the layered oxide material are solved, and the safety and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202411802177.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
The layered oxide materials in sodium ion batteries will have problems with Ni2+ and Fe3+ dissolution and gas production at high voltages, and the uneven deposition of sodium dendrites accelerates the capacity attenuation and short circuit of the battery.
The sodium electropositive electrode material including layered oxides and sodium lanthanum zirconium oxygen coating is used to alleviate Fe3+ dissolution and improve the specific capacity of the material through the formation and calcination of the lanthanum zirconium hydroxide coating.
It effectively alleviates the dissolution of Fe3+ in layered oxide materials, reduces the growth of dendrites, and improves the safety performance and cycle life of the battery.
Smart Images

Figure BDA0005178306370000111 
Figure BDA0005178306370000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium-ion positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion battery without a negative electrode. Background Art
[0002] Sodium ion batteries are batteries that use layered oxides (such as nickel-iron-manganese oxides), Prussian blue analogs (such as iron-based Prussian white, etc.), polyanions (such as sodium iron sulfate, sodium iron phosphate, etc.) as positive electrodes, and carbon materials (such as hard carbon, soft carbon) as negative electrodes. They mainly use esters and ethers as solvents. + The electrolyte is formed by metal salt (such as sodium fluoride salt, sodium borate salt and perchlorate, etc.) electrolyte and various additives (such as film-forming, flame retardant and overcharge protection, etc.).
[0003] Although layered oxides have the advantages of low cost, high safety and long cycle life, they will have Ni 2+ , Fe 3+ The serious problems of dissolution and gas production have become two inevitable problems. In addition, there is uneven deposition of sodium dendrites during the use of sodium-ion batteries, which accelerates the capacity decay and short circuit of the battery.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a sodium-ion positive electrode material and a preparation method thereof, a positive electrode sheet and a negative electrode-free sodium-ion battery, aiming to improve the safety and cycle life of the sodium-ion battery.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a sodium battery positive electrode material, comprising a layered oxide and a sodium lanthanum zirconium oxide coating layer coated on the layered oxide.
[0008] In an alternative embodiment, the chemical formula of the layered oxide is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0009] In an optional embodiment, the chemical formula of the sodium lanthanum zirconium oxide coating layer is Na7La3Zr2O 12 ;
[0010] Preferably, the mass proportion of the sodium lanthanum zirconium oxide coating layer in the sodium battery positive electrode material is 5%-10%.
[0011] In a second aspect, the present invention provides a method for preparing a sodium positive electrode material according to any one of the aforementioned embodiments, comprising: forming a lanthanum zirconium hydroxide coating layer on a layered oxide hydroxide precursor, and then mixing and calcining it with a sodium salt.
[0012] In an optional embodiment, the process of forming a lanthanum zirconium hydroxide coating layer includes: mixing a layered oxide hydroxide precursor, a complexing agent solution and a precipitant solution to obtain a reaction base liquid, adding a lanthanum source solution, a zirconium source solution and a precipitant solution to the reaction base liquid, so that the generated lanthanum zirconium hydroxide is coated on the layered oxide hydroxide precursor.
[0013] In an optional embodiment, the pH value of the reaction base solution is 11-12, and the concentration of the complexing agent is 11 g / L-13 g / L;
[0014] and / or, the concentration of the layered oxide hydroxide precursor in the reaction base solution is 0.08 Kg / L-0.15 Kg / L;
[0015] and / or, during the lanthanum-zirconium deposition process, controlling the reaction pH to 10-12 and the reaction temperature to 40° C.-80° C.;
[0016] and / or, during the lanthanum zirconium deposition process, under an inert atmosphere;
[0017] And / or, the precipitant solution is a sodium hydroxide aqueous solution with a concentration of 0.5 mol / L-2 mol / L;
[0018] And / or, the complexing agent solution is an aqueous ammonia solution.
[0019] In an optional embodiment, the concentration of the lanthanum source solution is 0.5mol / L-2mol / L, the concentration of the zirconium source solution is 0.5mol / L-2mol / L, the volume of the reaction base solution is 38L-45L, the total amount of the lanthanum source solution and the zirconium source solution introduced per hour is 1.5L-2.5L, and the introduction time is 9h-11h;
[0020] And / or, the lanthanum source in the lanthanum source solution is selected from at least one of lanthanum sulfate and lanthanum nitrate;
[0021] and / or, the zirconium source in the zirconium source solution is selected from at least one of zirconium sulfate and zirconium nitrate;
[0022] And / or, during the reaction process, the free metal salt solution in the reactor enters a concentrator for concentration, and then returns to the reactor to continue the reaction;
[0023] And / or, after the lanthanum-zirconium deposition is completed, solid-liquid separation is performed, and the obtained solid material is washed and dried.
[0024] In an optional embodiment, a layered oxide hydroxide precursor having a lanthanum zirconium hydroxide coating layer is mixed with a sodium salt and calcined, and the calcination temperature is controlled to be 700° C.-1000° C., and the calcination time is 20 h-30 h;
[0025] Preferably, the molar ratio of the total amount of lanthanum zirconium to the sodium in the sodium salt is controlled to be 1:(15-30);
[0026] Preferably, the sodium salt is selected from at least one of sodium carbonate and sodium hydroxide;
[0027] Preferably, after calcination, annealing is performed for 3 h to 5 h.
[0028] In a third aspect, the present invention provides a positive electrode sheet, comprising the sodium-based positive electrode material of any one of the aforementioned embodiments or the sodium-based positive electrode material prepared by any one of the preparation methods of the aforementioned embodiments.
[0029] In a fourth aspect, the present invention provides a negative electrode-free sodium ion battery, comprising the sodium ion battery positive electrode sheet of the aforementioned embodiment.
[0030] The present invention has the following beneficial effects: the inner layer of the sodium positive electrode material provided by the present invention is a layered oxide, and the outer layer is a sodium lanthanum zirconium oxide coating layer. The sodium lanthanum zirconium oxide coating layer can alleviate the Fe 3+ Dissolution phenomenon; Sodium lanthanum zirconium oxide material belongs to solid electrolyte and is a fast ion conductor of sodium ions. It can not only reduce the injection amount of electrolyte, reduce the growth of dendrites, increase the safety performance of the battery, but also improve the capacity of the active material. Based on the above advantages, the sodium positive electrode material provided by the present invention can improve battery safety and cycle life. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0032] Dendrite: Dendrites are crystals that grow in a typical multi-branched tree-like form. Dendrite growth is very common, similar to snowflake formations and frost patterns on windows.
[0033] Although sodium-ion batteries have the advantages of low cost, high safety and long cycle life, the layered oxide materials have a high Ni 2+ , Fe 3+The dissolution of sodium and the uneven deposition of sodium dendrites accelerate the capacity decay and short circuit of the battery, becoming two inevitable problems.
[0034] To this end, the embodiment of the present invention provides a sodium positive electrode material, including a layered oxide and a sodium lanthanum zirconium oxide coating layer coated on the layered oxide. By introducing the sodium lanthanum zirconium oxide coating layer, the Ni in the layered oxide material can be alleviated. 2+ , Fe 3+ Dissolution phenomenon improves the specific capacity of the material; Sodium lanthanum zirconium oxide material belongs to solid electrolyte and is a fast ion conductor of sodium ions. It can not only reduce the injection volume of electrolyte, reduce the growth of dendrites, increase the safety performance of the battery, but also improve the capacity of the active material.
[0035] In some embodiments, the layered oxide has the formula NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2. The chemical formula of the sodium lanthanum zirconium oxygen coating is Na7La3Zr2O 12 By optimizing the composition of the layered oxide and the sodium lanthanum zirconium oxide coating layer, especially adjusting the ratio of metal elements, the Fe content in the layered oxide material can be better alleviated. 3+ Dissolution phenomenon improves the electrochemical performance of the battery.
[0036] Furthermore, the mass ratio of the sodium lanthanum zirconium oxide coating layer in the sodium positive electrode material is 5%-10% (such as 5%, 6%, 7%, 8%, 9%, 10%), and the mass ratio of the sodium lanthanum zirconium oxide coating layer is preferably controlled within the above range, so that the formed coating layer is conducive to alleviating the Fe 3+ Dissolution phenomenon.
[0037] The present invention also provides a method for preparing a sodium positive electrode material, the steps of which are as follows:
[0038] S1. Providing layered oxide hydroxide precursor
[0039] According to the chemical formula of the layered oxide in the product, a layered oxide hydroxide precursor is provided so that the content of each metal element meets the requirements.
[0040] Specifically, according to the chemical formula of the layered oxide in the product, the layered oxide hydroxide precursor chemical formula provided is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH) 4. The layered oxide hydroxide precursor can be a commercially available material or can be prepared by a conventional co-precipitation method.
[0041] S2. Forming a lanthanum zirconium hydroxide coating layer
[0042] A lanthanum zirconium hydroxide coating layer is formed on the layered oxide hydroxide precursor. The formation method is not limited and the layered oxide hydroxide coating layer can be prepared by a co-precipitation method.
[0043] In some embodiments, when a lanthanum zirconium hydroxide coating layer is prepared by a co-precipitation method, the process of forming the lanthanum zirconium hydroxide coating layer includes: mixing a layered oxide hydroxide precursor, a complexing agent solution, and a precipitant solution to obtain a reaction base liquid, adding a lanthanum source solution, a zirconium source solution, and a precipitant solution to the reaction base liquid, so that the generated lanthanum zirconium hydroxide is coated on the layered oxide hydroxide precursor to form a uniform coating layer.
[0044] Furthermore, by adjusting the amount of complexing agent solution and precipitant solution, the pH value of the reaction base liquid is 10-12, the complexing agent concentration is 11g / L-13g / L, and the concentration of the layered oxide hydroxide precursor in the reaction base liquid is 0.08Kg / L-0.15Kg / L. Under this condition, lanthanum and zirconium can be more evenly deposited on the surface of the layered oxide hydroxide precursor. Specifically, the pH value of the reaction base liquid can be 10.0, 10.5, 11.0, 11.3, 11.5, 11.8, 12.0, etc.; the concentration of the complexing agent can be 11.0 g / L, 11.3 g / L, 11.5 g / L, 11.8 g / L, 12.0 g / L, 12.3 g / L, 12.5 g / L, 12.8 g / L, 13.0 g / L, etc.; the concentration of the layered oxide hydroxide precursor in the reaction base liquid can be 0.08 Kg / L, 0.10 Kg / L, 0.12 Kg / L, 0.15 Kg / L, etc.
[0045] In some embodiments, the precipitant solution is a sodium hydroxide aqueous solution with a concentration of 0.5 mol / L-2 mol / L, and the concentration of the sodium hydroxide aqueous solution can be 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, etc.; the complexing agent solution can be an ammonia aqueous solution, and its concentration is not limited. After adding, the ammonia concentration in the base liquid meets the requirements.
[0046] Furthermore, in order to control the lanthanum-zirconium deposition process, the reaction conditions of the coprecipitation and the feeding rate and other conditions were controlled: the concentration of the lanthanum source solution was 0.5mol / L-2mol / L, the concentration of the zirconium source solution was 0.5mol / L-2mol / L, the volume of the reaction base solution was 38L-45L, the total amount of the lanthanum source solution and the zirconium source solution introduced per hour was 1.5L-2.5L, and the introduction time was 9h-11h. By precisely controlling the concentration and introduction rate of the lanthanum source solution and the zirconium source solution, the precipitation rate was further controlled, the morphology and crystallinity of the lanthanum-zirconium hydroxide coating layer were controlled, and the formed lanthanum-zirconium hydroxide coating layer was made more uniform.
[0047] Specifically, the concentration of the lanthanum source solution refers to the concentration of lanthanum in the solution, which can be 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, etc.; the concentration of the zirconium source solution refers to the concentration of zirconium in the solution, which can be 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, etc. The volume of the reaction base solution can be 38 L, 40 L, 42 L, 45 L, etc.; the lanthanum source solution and the zirconium source solution can be of equal concentration, which makes it easier to control the ratio of lanthanum and zirconium introduced per unit time. The total amount of lanthanum source solution and zirconium source solution introduced per hour can be 1.5 L, 1.8 L, 2.0 L, 2.3 L, 2.5 L, etc., and the introduction time can be 9.0 h, 9.5 h, 10.0 h, 10.5 h, 11.0 h, etc.
[0048] Furthermore, the lanthanum source in the lanthanum source solution is selected from at least one of lanthanum sulfate and lanthanum nitrate, and the lanthanum source in the lanthanum source solution can be any one or more of the above; the zirconium source in the zirconium source solution is selected from at least one of zirconium sulfate and zirconium nitrate, and the zirconium source in the zirconium source solution can be any one or more of the above.
[0049] Furthermore, during the lanthanum zirconium deposition process, the process is carried out under an inert atmosphere, the reaction pH is controlled to be 11-12, and the reaction temperature is 40°C-80°C, and the lanthanum zirconium is deposited more quickly and evenly by adjusting the deposition conditions. Specifically, the type of inert gas is not limited, and it can be nitrogen, argon, etc.; during the deposition process, the pH value of the reaction system in the reactor can be controlled to be 11.0, 11.3, 11.5, 11.8, 12.0, etc.; the reaction temperature can be 40°C, 50°C, 60°C, 70°C, 80°C, etc.
[0050] In some embodiments, during the reaction process, the free metal salt solution in the reactor enters a concentrator for concentration, and the concentrator returns the concentrated metal salt solution to the reactor, and excess water is discharged from the reactor, thus preventing the waste of free metal salt.
[0051] Furthermore, after the lanthanum zirconium deposition is completed, solid-liquid separation is performed, and the obtained solid material is washed and dried. The solid-liquid separation can be performed by centrifugation, first using a sodium hydroxide solution for centrifugation, then centrifuging with deionized water for multiple times, and then placing it in an oven for drying. Specifically, the drying temperature can be 90°C-110°C, and the drying time is 10h-15h.
[0052] S3. Calcination
[0053] The layered oxide hydroxide precursor having a lanthanum zirconium hydroxide coating layer obtained in step S2 is mixed with a sodium salt and calcined to obtain a layered oxide in the inner layer and a sodium lanthanum zirconium oxide coating layer in the outer layer.
[0054] In some embodiments, a layered oxide hydroxide precursor having a lanthanum zirconium hydroxide coating layer is mixed with a sodium salt and calcined, the calcination temperature is controlled to be 700°C-1000°C, the calcination time is 20h-30h, and after the calcination is completed, annealing is performed for 3h-5h. The calcination temperature and time are preferably within the above range, so that the surface lanthanum zirconium hydroxide and the sodium salt react fully to form a sodium lanthanum zirconium oxygen coating layer on the surface.
[0055] Specifically, the calcination temperature can be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, etc.; the calcination time can be 20h, 23h, 25h, 28h, 30h, etc. After the calcination is completed, annealing is performed for 3h-5h, such as 3h, 4h, 5h, etc. The annealing here refers to annealing in stages after the calcination is completed, and the cooling is completed in 5h, such as the following temperature stages: 1000°C, 800°C, 600°C, 400°C, 200°C, and room temperature.
[0056] It should be noted that since the calcination temperature of sodium lanthanum zirconium oxide materials is close to 1000°C, among the commonly used sodium ion battery materials, only layered oxides can complete in-situ growth. Calcination of layered oxide hydroxide precursors and sodium lanthanum zirconium oxide hydroxide precursors together can reduce calcination costs.
[0057] Further, the molar ratio of the total amount of lanthanum zirconium to the sodium in the sodium salt is controlled to be 1: (15-30), such as 1: 15, 1: 18, 1: 20, 1: 23, 1: 25, 1: 28, 1: 30, etc. The amount of the sodium salt is preferably within this range, so that the sodium is slightly excessive. The sodium salt is selected from at least one of sodium carbonate and sodium hydroxide, and the sodium salt can be any one or more of the above.
[0058] An embodiment of the present invention provides a positive electrode sheet, including the sodium battery positive electrode material provided by the embodiment of the present invention, and may also include a positive electrode current collector, on which a positive electrode active coating containing the sodium battery positive electrode material provided by the embodiment of the present invention is formed.
[0059] An embodiment of the present invention also provides a negative electrode-free sodium ion battery, including the above-mentioned sodium ion battery positive electrode sheet, and may also include a negative electrode sheet, an electrolyte, a diaphragm, etc., to form a complete battery structure.
[0060] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0061] Example 1
[0062] This embodiment provides a method for preparing a sodium positive electrode material, the steps are as follows:
[0063] (1) Providing a layered oxide hydroxide precursor
[0064] The chemical formula of the layered oxide hydroxide precursor is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)3.
[0065] (2) Formation of a lanthanum zirconium hydroxide coating layer
[0066] After the reactor was cleaned, 40L of deionized water and 5kg of layered oxide hydroxide precursor were quantitatively added as seed crystals, the stirring of the reactor was adjusted to 30Hz and the temperature was set to 60°C, and the protective gas nitrogen was introduced at a rate of 6L / min. 1.9L of ammonia water with a mass fraction of 25% (the same below) was added to the reactor, the ammonia concentration was adjusted to 12.0g / L, 80mL of sodium hydroxide solution with a concentration of 1mol / L was added, and the pH was controlled at 11-12. The total volume of the reaction bottom liquid obtained was 41.98L, and the concentration of the layered oxide hydroxide precursor was 0.12Kg / L.
[0067] Reaction solution configuration: 1 mol / L sodium hydroxide aqueous solution; 1 mol / L lanthanum sulfate aqueous solution (lanthanum concentration is 1 mol / L) is selected as the lanthanum source; 1 mol / L zirconium sulfate (zirconium concentration is 1 mol / L) is selected as the zirconium source.
[0068] The reaction liquid is fed by a peristaltic pump, and a total of 20L of reaction liquid (total amount of lanthanum source and zirconium source) is consumed, and the reaction lasts about 10 hours (i.e., the feeding time is 10 hours). During the reaction, the free metal salt solution in the reactor will enter the concentrator, and the concentrator will return the concentrated metal salt solution to the reactor. The reaction pH value is controlled to be 11-12, and the reaction temperature is 60°C.
[0069] After the reaction was completed, the material was centrifuged, centrifuged once with a 1 mol / L sodium hydroxide solution, and centrifuged three times with deionized water at 60° C. Then, it was placed in a 100° C. oven and dried for 12 h.
[0070] (3) Calcination
[0071] The dried lanthanum zirconium hydroxide-coated layered oxide hydroxide precursor and sodium carbonate were mixed with a mixer for 1 hour, placed in a muffle furnace, calcined at 900°C in air for 25 hours, and annealed for 4 hours to obtain a solid electrolyte sodium lanthanum zirconium oxygen-coated layered oxide, wherein the molar ratio of the total amount of lanthanum zirconium to the sodium in the sodium salt is 1:15.
[0072] Example 2
[0073] This embodiment provides a method for preparing a sodium positive electrode material, the steps are as follows:
[0074] (1) Providing a layered oxide hydroxide precursor
[0075] The chemical formula of the layered oxide hydroxide precursor is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)3.
[0076] (2) Formation of a lanthanum zirconium hydroxide coating layer
[0077] After the reactor was cleaned, 40L of deionized water and 5kg of layered oxide hydroxide precursor were quantitatively added as seed crystals, the stirring of the reactor was adjusted to 40Hz and the temperature was set to 60°C, and the protective gas nitrogen was introduced at a rate of 6L / min. 1.9L of ammonia water was added to the reactor, the ammonia concentration was adjusted to 12.0g / L, 80mL of 1mol / L sodium hydroxide solution was added, and the pH was controlled at 10-11. The total volume of the reaction bottom liquid obtained was 41.98L, and the concentration of the layered oxide hydroxide precursor was 0.12Kg / L.
[0078] Reaction solution configuration: 1 mol / L sodium hydroxide aqueous solution; 1 mol / L lanthanum sulfate aqueous solution (lanthanum concentration is 1 mol / L) is selected as the lanthanum source; 1 mol / L zirconium sulfate (zirconium concentration is 1 mol / L) is selected as the zirconium source.
[0079] The reaction liquid was fed by a peristaltic pump, consuming a total of 20L of reaction liquid (the total amount of lanthanum source and zirconium source), and the reaction lasted about 10 hours. During the reaction, the free metal salt solution in the reactor will enter the concentrator, and the concentrator will return the concentrated metal salt solution to the reactor. The reaction pH value was controlled to be 11-12, and the reaction temperature was 60°C.
[0080] After the reaction was completed, the material was centrifuged, centrifuged once with a 1 mol / L sodium hydroxide solution, and centrifuged three times with deionized water at 60° C. Then, it was placed in a 100° C. oven and dried for 12 h.
[0081] (3) Calcination
[0082] The dried lanthanum zirconium hydroxide-coated layered oxide hydroxide precursor and sodium carbonate were mixed by a mixer for 1 hour, placed in a muffle furnace, calcined at 700°C in air for 30 hours, and annealed for 3 hours to obtain a solid electrolyte sodium lanthanum zirconium oxygen-coated layered oxide, wherein the molar ratio of the total amount of lanthanum zirconium to the sodium in the sodium salt is 1:20.
[0083] Example 3
[0084] This embodiment provides a method for preparing a sodium positive electrode material, the steps are as follows:
[0085] (1) Providing a layered oxide hydroxide precursor
[0086] The chemical formula of the layered oxide hydroxide precursor is Ni 1 / 3 Fe1 / 3 Mn 1 / 3 (OH)3.
[0087] (2) Formation of a lanthanum zirconium hydroxide coating layer
[0088] After the reactor was cleaned, 40L of deionized water and 5kg of layered oxide hydroxide precursor were quantitatively added as seed crystals, the stirring of the reactor was adjusted to 50Hz and the temperature was set to 60°C, and the protective gas nitrogen was introduced at a rate of 6L / min. 1.9L of ammonia water was added to the reactor, the ammonia concentration was adjusted to 12.0g / L, 80mL of 1mol / L sodium hydroxide solution was added, and the pH was controlled at 11-12. The total volume of the reaction bottom liquid obtained was 41.98L, and the concentration of the layered oxide hydroxide precursor was 0.12Kg / L.
[0089] Reaction solution configuration: 1 mol / L sodium hydroxide aqueous solution; 1 mol / L lanthanum sulfate aqueous solution (lanthanum concentration is 1 mol / L) is selected as the lanthanum source; 1 mol / L zirconium sulfate (zirconium concentration is 1 mol / L) is selected as the zirconium source.
[0090] The reaction liquid was fed by a peristaltic pump, consuming a total of 20L of reaction liquid (the total amount of lanthanum source and zirconium source), and the reaction lasted about 10 hours. During the reaction, the free metal salt solution in the reactor will enter the concentrator, and the concentrator will return the concentrated metal salt solution to the reactor. The reaction pH value was controlled to be 11-12, and the reaction temperature was 60°C.
[0091] After the reaction was completed, the material was centrifuged, centrifuged once with a 1 mol / L sodium hydroxide solution, and centrifuged three times with deionized water at 60° C. Then, it was placed in a 100° C. oven and dried for 12 h.
[0092] (3) Calcination
[0093] The dried lanthanum zirconium hydroxide-coated layered oxide hydroxide precursor and sodium carbonate were mixed with a mixer for 1 hour, placed in a muffle furnace, calcined at 1000°C in air for 20 hours, and annealed for 5 hours to obtain a solid electrolyte sodium lanthanum zirconium oxygen-coated layered oxide, wherein the molar ratio of the total amount of lanthanum zirconium to the sodium in the sodium salt is 1:30.
[0094] Example 4
[0095] The only difference from Example 1 is that the addition time of the reaction solution in step (2) is 5 hours.
[0096] Example 5
[0097] The only difference from Example 1 is that the addition time of the reaction solution in step (2) is 20 hours.
[0098] Example 6
[0099] The only difference from Example 1 is that the calcination temperature in step (3) is 500°C.
[0100] Example 7
[0101] The only difference from Example 1 is that the calcination temperature in step (3) is 1500°C.
[0102] Comparative Example 1
[0103] This comparative example provides a method for preparing a conventional sodium positive electrode material, and the specific steps are as follows:
[0104] (1) Providing a layered oxide hydroxide precursor
[0105] Same as step (1) in Example 1.
[0106] (2) Calcination
[0107] The layered oxide hydroxide precursor and sodium carbonate were mixed by a mixer for 1 hour, placed in a muffle furnace, calcined at 900° C. in air for 25 hours, and annealed for 4 hours. The molar ratio of the total amount of metal elements in the layered oxide hydroxide precursor to the sodium in the sodium salt was 1:1.
[0108] Comparative Example 2
[0109] The coating method of the lanthanum-zirconium coating layer in this comparative example is different, and the specific steps are as follows:
[0110] Prepare a layered oxide positive electrode material according to the method of Comparative Example 1;
[0111] Lanthanum acetate and zirconium acetate are dissolved in ethanol, and then layered oxide positive electrode materials are added and slowly evaporated at 80°C to form a gel; the obtained gel is vacuum dried and crushed at 120°C, and then calcined at 550°C for 6 hours to obtain La2Zr2O7-coated layered oxide sodium positive electrode material.
[0112] Test Example 1
[0113] The electrochemical properties of the sodium positive electrode materials prepared in the test examples and comparative examples are shown in Table 1.
[0114] Test method: The materials provided in the examples and comparative examples are used as positive electrode active materials, N-methylpyrrolidone is used as solvent, and the solid material composition is positive electrode active material, PVDF (polyvinylidene chloride), SP (carbon black) and PVP (polyvinyl pyrrolidone). The mass ratio of positive electrode active material, PVDF, SP and PVP is 100:7:10:3. The positive electrode is coated. The positive electrode slurry is coated on the aluminum foil @ sodium fluoroaluminate / sodium fluorosilicate current collector prepared in this example, and the coating amount is controlled to be 20g / cm 2 , followed by drying;
[0115] A negative electrode-free battery is selected, and a carbon-coated aluminum foil current collector is used; the separator is a commercial dry PP base film, which is injected with an ether electrolyte and made into a soft-pack battery cell by a lamination process. The electrolyte is 1M sodium salt NaPF6 + solvent (diethylene glycol dimethyl ether).
[0116] Table 1 Performance test results of sodium positive electrode materials prepared in Examples and Comparative Examples
[0117]
[0118]
[0119] It can be seen from Table 1 that the electrochemical performance of the sodium positive electrode material prepared in the embodiment of the present invention is significantly better than that of the comparative example.
[0120] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A sodium positive electrode material, characterized in that: The invention comprises a layered oxide and a sodium lanthanum zirconium oxide coating layer coated on the layered oxide.
2. The sodium positive electrode material according to claim 1, characterized in that The chemical formula of the layered oxide is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
3. The sodium positive electrode material according to claim 1, characterized in that The chemical formula of the sodium lanthanum zirconium oxygen coating layer is Na7La3Zr2O 12 ; Preferably, the mass proportion of the sodium lanthanum zirconium oxide coating layer in the sodium battery positive electrode material is 5%-10%.
4. A method for preparing the sodium positive electrode material according to any one of claims 1 to 3, characterized in that: include: A lanthanum zirconium hydroxide coating layer is formed on a layered oxide hydroxide precursor, which is then mixed with a sodium salt and calcined.
5. The preparation method according to claim 4, characterized in that: The process of forming a lanthanum zirconium hydroxide coating layer includes: mixing a layered oxide hydroxide precursor, a complexing agent solution and a precipitant solution to obtain a reaction base solution, adding a lanthanum source solution, a zirconium source solution and a precipitant solution to the reaction base solution, and coating the generated lanthanum zirconium hydroxide on the layered oxide hydroxide precursor.
6. The preparation method according to claim 5, characterized in that: The pH value of the reaction base solution is 11-12, and the concentration of the complexing agent is 11g / L-13g / L; and / or, the concentration of the layered oxide hydroxide precursor in the reaction base solution is 0.08 Kg / L-0.15 Kg / L; and / or, during the lanthanum-zirconium deposition process, controlling the reaction pH to 10-12 and the reaction temperature to 40° C.-80° C.; and / or, during the lanthanum zirconium deposition process, under an inert atmosphere; And / or, the precipitant solution is a sodium hydroxide aqueous solution with a concentration of 0.5 mol / L-2 mol / L; And / or, the complexing agent solution is an aqueous ammonia solution.
7. The preparation method according to claim 5, characterized in that: The concentration of the lanthanum source solution is 0.5mol / L-2mol / L, the concentration of the zirconium source solution is 0.5mol / L-2mol / L, the volume of the reaction base solution is 38L-45L, the total amount of the lanthanum source solution and the zirconium source solution introduced per hour is 1.5L-2.5L, and the introduction time is 9h-11h; And / or, the lanthanum source in the lanthanum source solution is selected from at least one of lanthanum sulfate and lanthanum nitrate; And / or, the zirconium source in the zirconium source solution is selected from at least one of zirconium sulfate and zirconium nitrate; And / or, during the reaction process, the free metal salt solution in the reactor enters a concentrator for concentration, and then returns to the reactor to continue the reaction; And / or, after the lanthanum zirconium deposition is completed, solid-liquid separation is performed, and the obtained solid material is washed and dried.
8. The preparation method according to claim 4, characterized in that: The layered oxide hydroxide precursor having a lanthanum zirconium hydroxide coating layer is mixed with a sodium salt and calcined, the calcination temperature is controlled to be 700° C.-1000° C., and the calcination time is 20 h-30 h; Preferably, the molar ratio of the total amount of lanthanum and zirconium to the sodium in the sodium salt is controlled to be 1:(15-30); Preferably, the sodium salt is selected from at least one of sodium carbonate and sodium hydroxide; Preferably, after calcination, annealing is performed for 3 h to 5 h.
9. A positive electrode sheet, characterized in that: The invention comprises the sodium positive electrode material described in any one of claims 1 to 3 or the sodium positive electrode material prepared by the preparation method described in any one of claims 4 to 8.
10. A negative electrode-free sodium ion battery, characterized in that: Including the sodium ion battery positive electrode sheet as described in claim 9.
Citation Information
Cited By
LLZAO-coated sodium ion battery layered transition metal oxide positive electrode material
CN120199809A
Sodium-ion battery positive electrode material, preparation method thereof and battery
CN120895604A